2018
DOI: 10.14283/jfa.2018.15
|View full text |Cite
|
Sign up to set email alerts
|

Examining Differences in Recovery Outcomes Between Male and Female Hip Fracture Patients: Design and Baseline Results of a Prospective Cohort Study From the Baltimore Hip Studies

Abstract: Background: Incidence of hip fractures in men is expected to increase, yet little is known about consequences of hip fracture in men compared to women. It is important to investigate differences at time of fracture using the newest technologies and methodology regarding metabolic, physiologic, neuromuscular, functional, and clinical outcomes, with attention to design issues for recruiting frail older adults across numerous settings. Objectives: To determine whether at least moderately-sized sex differences exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…4 More baseline comorbidity among men compared to women may explain greater allcause mortality in men because comorbid conditions prior to fracture have been consistently demonstrated to predict postfracture mortality. 2,20 Lower cognitive function at hospital admission among men than women could also explain their higher all-cause mortality rate since it has been shown that impaired cognition is associated with allcause mortality at 6-months after hip fracture. 6 However, both comorbidity and cognitive function were adjusted for in the models, so they are not likely to explain men's increased mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 More baseline comorbidity among men compared to women may explain greater allcause mortality in men because comorbid conditions prior to fracture have been consistently demonstrated to predict postfracture mortality. 2,20 Lower cognitive function at hospital admission among men than women could also explain their higher all-cause mortality rate since it has been shown that impaired cognition is associated with allcause mortality at 6-months after hip fracture. 6 However, both comorbidity and cognitive function were adjusted for in the models, so they are not likely to explain men's increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Further details regarding the study design and methodology are available elsewhere. 2 The BHS-7 cohort enrolled 339 participants (168 men and 171 women) and was restricted to an analytic cohort of 300 participants (145 men, 155 women) with complete data on salient variables measured at baseline.…”
Section: Why Does This Paper Matter?mentioning
confidence: 99%
“…The Baltimore Hip Studies (BHS) began in 1983 to study outcomes in older adults with hip fractures. The BHS assessed recovery among hip fracture patients within five cohort studies (BHS1 9 , BHS2 6 , BHS3 21 , BHS6 22 , BHS7 23 ) and two randomized controlled trials (BHS4 24 and BHS5 25 ). These studies were approved by the Institutional Review Boards of the University and the individual study hospitals where recruitment took place.…”
Section: Study Samplementioning
confidence: 99%
“…Patients were excluded if not community-dwelling at the time of fracture, non-English speaking, bedbound for 6 months or more prior to fracture, lived >70 miles from the hospital, weighed >300 pounds, did not have surgical hip repair, or had hardware in the contralateral hip. 13 BHS-7 oversampled males by frequency-matching the enrollment of females to males by hospital and time of admission yielding approximately 50% male sample (male = 168; female = 171). Proxies provided data on the patient's behalf if participants scored <36 on the 3MS.…”
Section: Samplementioning
confidence: 99%
“…Proxies provided data on the patient's behalf if participants scored <36 on the 3MS. 13 Nine participants were excluded due to missing medical record abstraction information (1 male) or a baseline 3MS (4 females, 4 males). Thus, the analytic sample was 330 (163 males, 167 females).…”
Section: Samplementioning
confidence: 99%